2022
DOI: 10.1002/slct.202203094
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Antibacterial Activity of Calcium Hydroxide Nanoparticles Against Gram‐Positive and Gram‐Negative Bacteria

Abstract: Calcium hydroxide nanoparticles (Ca(OH)2 NPs) are of great interest in the development of new products due to their antibacterial properties. Chemical precipitation process was used for synthesizing Ca(OH)2 NPs. The synthesized Ca(OH)2 NPs were characterized by using X‐ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Fourier Transmission Infrared Spectroscopy (FTIR), UV‐Visible spectroscopy, DLS (Dynamic Light Scattering) techniques. Ca(OH)2 NPs were assessed for antibacterial activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Cobalt nanoparticles and NiNPs have been found to possess antibacterial properties, which make them attractive for use in medical and industrial applications. Research studies have shown that these nanoparticles can effectively inhibit the growth and proliferation of bacteria of several types, encompassing Gram-positive and Gram-negative ones (Fazal et al 2022;Harish et al 2022;Sarian et al 2022;Hassan Afandy et al 2023). The antibacterial properties of these nanoparticles are thought to be due to their ability to generate reactive oxygen species (ROS) that can damage bacterial cell membranes and inhibit bacterial growth (Saravanan et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt nanoparticles and NiNPs have been found to possess antibacterial properties, which make them attractive for use in medical and industrial applications. Research studies have shown that these nanoparticles can effectively inhibit the growth and proliferation of bacteria of several types, encompassing Gram-positive and Gram-negative ones (Fazal et al 2022;Harish et al 2022;Sarian et al 2022;Hassan Afandy et al 2023). The antibacterial properties of these nanoparticles are thought to be due to their ability to generate reactive oxygen species (ROS) that can damage bacterial cell membranes and inhibit bacterial growth (Saravanan et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, as a widely applied antimicrobial medicament, the highly alkaline calcium hydroxide generated from the reactions could also promote the remineralization and therapeutic recovery of tooth hard tissue. [ 37,38 ] It could be hypothesized that the proposed microbombs can be activated by US to synergistically achieve ROS‐induced bacteria inactivation and bubble‐assisted dental plaque disruption for caries prevention as well as biofilm‐related diseases treatments (Scheme 1C).…”
Section: Introductionmentioning
confidence: 99%